Ergometer-cycling with strict versus minimal contact supervision among the oldest adults: A cluster-randomised controlled trial. (May 2017) - Van Roie, Evelien; Martien, Sofie; Hurkmans, Emalie; Pelssers, Johan; Seghers, Jan; Boen, Filip; Delecluse, Christophe
Highlights: Ergometer-cycling with minimal coach-supervision is feasible in residential homes. Autonomy support does not result in better long-term adherence rates. High adherers show positive but small effects on physical and muscular function. Abstract: Objective: To evaluate the feasibility and short- and long-term effects of two 10-wk structured ergometer-cycling programs among elderly in assisted-living residences. Design, setting, and participants: Eight assisted-living residences (N = 95; age = 81.2 ± 5.9 years) were randomly assigned to one of three conditions: 1) ergometer-cycling with strict coach-supervision (STRICT, N = 3; n  = 35); 2) ergometer-cycling with autonomy-supportive minimal contact coach-supervision (AUT; N = 3; n  = 36); or 3) control condition (CON; N = 2, n  = 24). Intervention: Three-weekly progressive ergometer-cycling sessions for 10 weeks. Main outcome measures: Feasibility, physical activity (PA), muscular strength, functional performance and quality of life (baseline, post-intervention (10weeks) and 6-month follow-up). Results: 83 participants were analyzed post-intervention, 75 at follow-up. Adherence was higher in STRICT than AUT during the intervention ( p  = 0.001), but not during follow-up. Compared with CON, both programs showed positive short- and long-term effects on moderate-intensity PA ( p  = 0.034). With regard to strength, functional performance and well-being, no time-by-group interaction effects were found. When comparing high-adherers (adherence ≥ 80%) to low-adherers, a greater increase in functional performance and in well-being and a trend towards a lower decrease in strength were found in the short-term ( p  = 0.047, p  < 0.001 and p  = 0.054, respectively). Conclusion: Both interventions were feasible and equally effective to increase long-term engagement in PA, irrespective of the type of supervision. When adherence is high, positive effects on strength, performance and well-being can be expected.